Modeling the effects of dust‐radiative forcing on the movement of Hurricane Helene (2006). (8th April 2015) - Chen, Shu‐Hua; Liu, Yi‐Chin; Nathan, Terrence R.; Davis, Christopher; Torn, Ryan; Sowa, Nicholas; Cheng, Chao‐Tzuen; Chen, Jen‐Ping
Abstract : The influence of direct dust‐radiative forcing on the movement and track of Hurricane Helene (2006) is examined numerically using the Weather Research and Forecasting dust model. Numerical simulations show that the model‐generated dust plume modifies the thermal field, causing a clockwise turning of the vertical shear surrounding the plume, which changes the deep layer steering flow. The change in the steering flow modifies Helene 's moving speed and direction as it transits the plume. As Helene exits the plume, it has a different trajectory than it would have had in the absence of dust‐radiative forcing. Consequently, the difference in the tracks with and without dust‐radiative forcing continues to grow with distance from the plume. The dust‐induced changes in temperature and wind together cause Helene 's modeled storm track to be in closer agreement with the observed track; the dust‐radiative forcing reduces the error in the model's 7‐day track forecasts by an average of 27% (∼205 km).